MODEL PERUBAHAN DAN ARAHAN PENGGUNAAN LAHAN UNTUK MENDUKUNG KETERSEDIAAN BERAS DI KABUPATEN BREBES DAN KABUPATEN CILACAP - Andreas Ari Putro Dwinanto; Khursatul Munibah; Untung Sudadi (Diponegoro University, 2016)
The increasing of paddy field change has threatened the fulfillment of rice needs. The objective of this research is to analyze the spatial pattern of land use change, to predict land use change in 2030, to arrange rice availability balance sheet in 2030 and to arrange land use direction to support rice availability in Brebes and Cilacap Regencies. The rate of paddy field change started from 2005 till 2015 in Brebes regency higher than the rate of change in Cilacap. Land use change model is built using cellular automata (CA) approach. The prediction in 2030 have shown settlements will be growing while the paddy field will have more high pressure. The prediction of paddy field in both of Regency. The calculation in 2030 shows that either Brebes regency or Cilacap regency has already surplus with the amount of rice surplus from year to year constantly will decrease. To maintain the rice availability, paddy field is directed to be protected. Shrub and mix crop are directed to be paddy field to increase rice production